PERLINDUNGAN HAK BAGI KREDITUR DALAM PERJANJIAN SEWA GUNA USAHA (Jurnal De Jure Muhammadiyah Cirebon, 2024)
Leasing has become a growing business activity in Indonesia, mainly due to its flexibility in meeting the capital and asset needs of business operators. This activity is carried out through an agreement between the creditor (lessor) and the debtor (lessee), which serves as the legal basis for defining the rights and obligations of both parties. However, in practice, there are frequent violations of the agreement terms, wherein the debtor commits a breach that causes losses to the creditor. This study adopts a normative juridical approach, utilizing literature sources and other relevant references. The research findings indicate that legal protection for creditors in leasing agreements can be realized through the right to claim compensation, request contract termination, and shift the risk of loss to the debtor upon the occurrence of a breach. These provisions aim to protect creditors from potential losses and ensure the fulfillment of their rights. With clear legal protections in place, creditors can be better safeguarded and shielded from the risks arising from debtor defaults.Keywords: Agreement, Leasing, Breach